Konstruksi Makna Hikmah dalam Al-Qur’an dan Arif dalam Psikologi Barat: Studi Komparatif - Mundzir, Ilham (AL QUDS : Jurnal Studi Alquran dan Hadis, 2023)
Construction of the Meaning of Hikmah in the Qur'an and Wisdom in Western Psychology: A Comparative Study Although there have been many studies examining the psychology of wisdom with religious and cultural perspectives, research on the psychology of wisdom in the perspective of the Qur'an is very rare. This article aims to analyze and find the construction of the meaning of hikmah in the al-Qur’an and compare it with the psychology of wisdom in the perspective of Western psychology in order to find similarities and differences. Using a qualitative approach, this article explores the word hikmah in Qur'an with its exegesis using al-Qur’an al-Bahis apps and studies literature on the psychology of wisdom. The data source is processed by content analysis. The results of the study found that there were similarities and differences between wisdom in the Qur'an and the psychology of wisdom in psychology. Wisdom in Islam is not only a gift from Allah but is also oriented to worship, carry out Allah's commands and stay away from His prohibitions. While wisdom in psychology is more obtained by being cultivated through learning and experience and is oriented to solving everyday worldly problems. This study is useful in complementing, enriching the theory and practice of the psychology of wisdom that is currently developing.